Minimizing Risks of Invasive Alien Plant Species in Tropical Production Forest Management - Padmanaba, M.; Corlett, Richard T. (MDPI, 2014)
Timber production is the most pervasive human impact on tropical forests, but studies of logging impacts have largely focused on timber species and vertebrates. This review focuses on the risk from invasive alien plant species, which has been frequently neglected in production forest management in the tropics. Our literature search resulted in 114 publications with relevant information, including books, book chapters, reports and papers. Examples of both invasions by aliens into tropical production forests and plantation forests as sources of invasions are presented. We discuss species traits and processes affecting spread and invasion, and silvicultural practices that favor invasions. We also highlight potential impacts of invasive plant species and discuss options for managing them in production forests. We suggest that future forestry practices need to reduce the risks of plant invasions by conducting surveillance for invasive species; minimizing canopy opening during harvesting; encouraging rapid canopy closure in plantations; minimizing the width of access roads; and ensuring that vehicles and other equipment are not transporting seeds of invasive species. Potential invasive species should not be planted within dispersal range of production forests. In invasive species management, forewarned is forearmed.